Desolvation‐Triggered Versatile Transfer‐Printing of Pure BN Films with Thermal–Optical Dual Functionality. Issue 38 (16th August 2020) - Han, Yujin; Han, Hyeuk Jin; Rah, Yoonhyuk; Kim, Cheolgyu; Kim, Moohyum; Lim, Hunhee; Ahn, Kwang Ho; Jang, Hanhwi; Yu, Kyoungsik; Kim, Taek‐Soo; Cho, Eugene N.; Jung, Yeon Sik
Abstract: Although hexagonal boron nitride (BN) nanostructures have recently received significant attention due to their unique physical and chemical properties, their applications have been limited by a lack of processability and poor film quality. In this study, a versatile method to transfer‐print high‐quality BN films composed of densely stacked BN nanosheets based on a desolvation‐induced adhesion switching (DIAS) mechanism is developed. It is shown that edge functionalization of BN sheets and rational selection of membrane surface energy combined with systematic control of solvation and desolvation status enable extensive tunability of interfacial interactions at BN–BN, BN–membrane, and BN–substrate boundaries. Therefore, without incorporating any additives in the BN film and applying any surface treatment on target substrates, DIAS achieves a near 100% transfer yield of pure BN films on diverse substrates, including substrates containing significant surface irregularities. The printed BNs demonstrate high optical transparency (>90%) and excellent thermal conductivity (>167 W m −1 K −1 ) for few‐micrometer‐thick films due to their dense and well‐ordered microstructures. In addition to outstanding heat dissipation capability, substantial optical enhancement effects are confirmed for light‐emitting, photoluminescent, and photovoltaic devices, demonstrating their remarkable promise for next‐generation optoelectronic device platforms. Abstract : A facile approach to print a pure boron nitride (BN) film with both high thermal conductivity (≈167 W m −1 K −1 ) and optical transparency (≈90%) on various substrates is developed based on desolvation‐induced adhesion switching. This approach allows near‐perfect transfer yield (≈100%) while ensuring good interfacial contact, realizing the full potential of the thermal and optical properties of BN for practical devices.